Nursing care at critical care patient inter-hospital transfer - Catarina Carvalho; Joana Pereira Sousa (Instituto Politécnico de Viseu, 2022)
Introduction: In inter-hospital transport of the critically ill patient, safety measures have to be addressed by the nurse who follows the patient's clinical situation with accurate clinical information. Objective: Map the items in the inter-hospital transport checklist. Methods: A scoping review will be conducted according to the latest Joanna Briggs Institute (J.B.I.) guidelines regarding methodology. A range of relevant electronic databases and grey literature will be searched using terms such as critically ill, inter-hospital transport, patient transfer, checklist, and guidelines. Results: This scoping review will consider any type of quantitative, qualitative, and mixed methods study, focusing on items to include in a checklist for monitoring the critically ill patient in inter-hospital transport. Conclusion: The development and implementation of an inter-hospital transport checklist enable safety during patient transfer. Nurses are the healthcare professionals that mostly accompany critically ill patients between different hospital levels of care. This protocol is registered in the Open Science Framework.